Post COVID-19, still wear a face mask? Self-perceived facial attractiveness reduces mask-wearing intention - Cha, Seung Eun; Ku, Xyle; Choi, Incheol (Frontiers in Psychology, 2023)
With the emerging post-COVID era, wearing face masks has become a domain of personal choice. Then, who wants to continue wearing a mask when it is no longer mandatory? In this article, we expect and examine the role of self-perceived attractiveness in predicting mask-wearing intention and its mechanism across three studies (total N = 1,030). Studies 1 and 2 demonstrated that individuals with high (vs. low) self-perceived attractiveness were less willing to wear a mask, due to a weaker endorsement of the belief that mask-wearing enhances their perceived attractiveness (i.e., mask attractiveness belief). Study 3 further revealed that this mediational association was stronger in situations where the need to deliver a favorable impression was high (job interview context) versus low (walking a dog context). Overall, we provide a novel finding that self-perceived attractiveness has significant effects on mask-wearing intention via mask attractiveness belief in the post-pandemic of COVID-19. Our findings suggest that mask-wearing can shift from being a self-protection measure during the COVID-19 pandemic to a self-presentation tactic in the post-pandemic era.